HISTOMORPHOLOGICAL EFFECTS OF HUNGER STRESS ON OVARIES - Yousaf, Maria; Siddiqi, Hina; Waheed, Nazish (Journal of Ayub Medical College Abbottabad, 2017)
Background: Incidence of stress is on the rise in our daily life involving various neurobiological, endocrinological and behavioral changes. Hunger stress has a potent influence on mental, physical, and reproductive health by affecting the hypothalamic-pituitary gonadal axis. Methods: It was a laboratory based randomized control trial. Adult female mice (BALB-c strain) weighing 25-27 grams on first day of estrous cycle were taken in two groups (ten each). Group A was kept in normal environment of animal house for one month. Group B was given hunger stress by restricting the diet to about 50% per day for one month. Right ovaries of the animals were dissected out and observed for shape, color, and weight. Histological slides were prepared for the count of primary, secondary, and tertiary follicles. Results: Statistically significant decrease in animal and ovary weight with significant fall in ovarian follicles was observed. Conclusion: Hunger stress affects the ovaries by reducing its weight and number of follicles. Keywords: Stress; Hunger; Ovarian follicles; Ovary